Estrategia Metodológica de Aprendizaje por Descubrimiento, para la enseñanza de Estudios Sociales, Bloque I: Historia e Identidad, de octavo año EGB. - Guashpa Gabin, Iván Fernando (2023)
This research work entitled "Methodological strategy of learning by discovery, for the teaching of Social Studies, Block I: History and identity, of eighth grade EGB" aimed to respond to the educational needs presented in the subject of Social Studies. This research project uses a logical methodology, a mixed approach (qualitative and quantitative), and a case report-type descriptive design. The data collection techniques and instruments include surveys and interviews directed to teachers and students of the Eighth Year of EGB in Social Studies, particularly in Block I: History and Identity. The study population is the "Pedro Vicente Maldonado" Educational Unit, and the sample consists of 25 students and two teachers from that institution. Finally, taking into consideration the results obtained and according to the identified need for innovative strategies to be applied in the classroom, through this research, several methodological approaches are proposed to favor and strengthen the teaching and learning process of students concerning the subject of Social Studies and thus, achieve the objectives established in the curriculum.